The authority of planners as seen by the common population: representations in popular music (São Paulo, Brazil) - Silva, Marcos (International Planning History Society Proceedings, 2016)
This paper aims at examining the images and discourses related to the figure of the urban planner or manager as seen by the common population, especially the poorer inhabitants of the city of São Paulo (Brazil) during the 1950's and 1960's. The general purpose is to establish a contrast between the usually celebrated image of urban planners as professionals devoted to the “common good”, and the popular perception that they often adopt an authoritarian approach towards the people, their lifestyles or identity places. For that purposes, the study examines a series of popular songs recorded during the period and, by means of a discourse analysis of their lyrics, investigates the representations of the urban authorities found in popular music. With privilege given to sambas, composed by artists such as Adoniran Barbosa, Paulo Vanzolini and others, the paper assumes that the narratives of the songs represent a set of common and identifiable perceptions of the public in relation to the authorities. Although not intended to be accurate testimonials, the songs can be seen as legitimate evidences of the tensions or conflicts between the common people and the establishment, as seen from the point of view of these people. The songs can illustrate the forms by which the population dealt with the authority of State (represented by the planner, who the artists usually name as "Doctor") in situations of urban reforms and resettlement. The main finding of the study is that, for most of the "ordinary people", the planner does not always intend to satisfy the needs of the whole population of a city when designing the urban transformations – instead, he is simply an authority to which the inhabitants must submit. In addition, the transformations of the city means frequently the loss of places of memory, sociability and identity, since the small, local features of a place are usually disregarded in favour of a large-scale view of city management.